Six Sigma Analyze Phase for New Product Development Prototype Process Improvement - Sabri Mohamad Zin, Mohd; Rahman Mahmood, Ab; Hasrulnizzam Wan Mahmood, Wan; Rahim, Fadhlur (International Journal of Engineering and Technology, 2018)
Many manufacturing companies focus on the innovative product. Prototyping process plays a very important role for innovative product because prototype helps the company to test the functionality and stability of a product. The popularity of the product on the market also can be done by using prototype to determine the customer interest on the product. This study is conducted at research and development department of a stationeries products company. The purpose of this study is to reduce the total duration of prototyping process by using Six Sigma phase. This article focusing on analyse phase of this study where the cause and effect diagram, failure mode and effect analysis and pareto chart were used to determine the major causes of the problem. Once the major causes were identified, a solution plan was proposed in Improve phase. Results and findings for this analyze phase explaining about top level process overview to visualize the whole research and development structure interaction with prototyping process and how cause and effect diagram being further elaborate focusing on poor prototyping process visibility and process duration too long.Â